Genome-Wide Analysis of Oceanimonas sp. GK1 Isolated from Gavkhouni Wetland (Iran) Demonstrates Presence of Genes for Virulence and Pathogenicity - Parsa Yeganeh, Laleh (Cell J, 2015)
OBJECTIVE: The bacterium Oceanimonas sp. (O. sp.) GK1 is a member of the Aeromonadaceae family and its genome represents several virulence genes involved in fish and human pathogenicity. In this original research study we aimed to identify and characterize the putative virulence factors and pathogenicity of this halotolerant marine bacterium using genome wide analysis. MATERIALS AND METHODS: The genome data of O. sp. GK1 was obtained from NCBI. Comparative genomic study was done using MetaCyc database. RESULTS: Whole genome data analysis of the O. sp. GK1 revealed that the bacterium possesses some important virulence genes (e.g. ZOT, RTX toxin, thermostable hemolysin, lateral flagella and type IV pili) which have been implicated in adhesion and biofilm formation and infection in some other pathogenic bacteria. CONCLUSION: This is the first report of the putative pathogenicity of O. sp.GK1. The genome wide analysis of the bacterium demonstrates the presence of virulence genes causing infectious diseases in many warmand cold-blooded animals.